(untitled) (Práxis Educativa, 2018)
This is a paper whose main objective is to present the results of an exploratory research carried out through the sending of a web questionnaire, whose purpose was to survey the opinions of researchers - leaders and vice leaders of research groups - in the area of Education in the five Regions of Brazil on the process of regulating conduct in research in the educational field as part of the Human, Social and Applied Social Sciences (known as CHSSA), currently represented by the Resolution of the National Health Council no. 510/2016. The structure of the questionnaire could be grouped in three parts: the first one with closed questions of characterization of the researcher and the respective Research Group; the second with closed questions entering more precisely the research problem; and the third with open questions, seeking to collect higher quantity and quality of data for analysis. This paper follows the order of the questionnaire, seeking to provide an overview of the researchers’ perception of the educational field about the aforementioned normative that currently regulates behavior in research. As main results regarding the research problem it is possible to point out a dissatisfaction amongst the researchers of the educational field with the current regulation proceeded by the previously mentioned Resolution that follows a tradition of norms with influence of the area of the Health Sciences. Keywords: Ethics and education. Education and regulation. Resolution CNS no. 510/2016.